Rights and Responsibilities - Grace Jones (India Crabtree Publishing Company, 2018)
"What are moral and legal rights and how are they recognized in our society? This engaging title explores what having 'rights' means, while pointing out that we can't have rights without also having responsibilities. A discussion about standing up for your rights will help readers understand the importance of individual rights and how they must be protected"--
Keywords: PY - UOI - How we Organize Ourselves; Government